2019
DOI: 10.1101/708024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Versatile multi-transgene expression using improved BAC TG-EMBED toolkit, novel BAC episomes, and BAC-MAGIC

Abstract: 16Achieving reproducible, stable, and high-level transgene expression in 17 mammalian cells remains problematic. Previously, we attained copy-number-18 dependent, chromosome-position-independent expression of reporter minigenes 19 by embedding them within a BAC containing the mouse Msh3-Dhfr locus (DHFR 20 BAC). Here we extend this "BAC TG-EMBED" approach. First, we report a 21 toolkit of endogenous promoters capable of driving transgene expression over a 22 novel gene circuits, involving the expression of mul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…We found the presence of nonintegrated BAC transgenes propagating as episomes and their unequal segregation to be the source of this heterogeneity. The formation and propagation of BAC episomes are beyond the scope of the present study and are reported elsewhere . In the absence of continued drug selection, we would expect cells that have lost BAC transgenes will accumulate if there is any selective growth advantage for cells with fewer BAC copies.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We found the presence of nonintegrated BAC transgenes propagating as episomes and their unequal segregation to be the source of this heterogeneity. The formation and propagation of BAC episomes are beyond the scope of the present study and are reported elsewhere . In the absence of continued drug selection, we would expect cells that have lost BAC transgenes will accumulate if there is any selective growth advantage for cells with fewer BAC copies.…”
Section: Resultsmentioning
confidence: 89%
“…The formation and propagation of BAC episomes are beyond the scope of the present study and are reported elsewhere. 50 In the absence of continued drug selection, we would expect cells that have lost BAC transgenes will accumulate if there is any selective growth advantage for cells with fewer BAC copies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%